Humanizing Discipline: The Impact of Empathetic Communication on Inmate Rehabilitation - Adi Sucipto; Ahmad Tamrin Sikumbang; Hasnun Jauhari Ritonga (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims For analyze impact communication empathetic to rehabilitation inhabitant foster care in correctional institutions Class II-A Binjai . This study uses method qualitative descriptive , with informants consisting of from three category main : citizen foster , officer institution correctional , and head institution correctional . Informant chosen using purposive sampling to get view deep related to the coaching process . Data is analyzed use analysis thematic with NVivo software assistance , which focuses on patterns communication and its impact to discipline . The theory used is the FIRO (Fundamental Interpersonal Relations Orientation) Theory, which highlights importance inclusion , control , and affection in interpersonal relationships . Research results show that communication empathetic increase involvement inhabitant foster in the rehabilitation program , reducing conflict , and strengthen interpersonal relationships , so that create environment conducive for change behavior .